"Impact resistance of silicone rubber/fiber composites for structural protection" - ZHANG Song， LIU Yan-hui (Hecheng xiangjiao gongye)
The dynamic mechanical properties of silicone rubber/fiber composites under different strain rates were investigated using Hopkinson pressure bar technique. The results showed that there was a linear relationship between gas pressure and strain rate, and the superimposed waveform of incident wave strain and reflected wave strain were consistent with the waveform of transmitted wave strain, which proved that the composites were in dynamic stress equilibrium, and the stress equilibrium could be maintained during the loading process. The stress and energy absorption capacity of the composites both increased with the increase of strain rate, and the stress-strain curves and the dynamic modulus had an obvious strain rate effect.